Pelatihan Inspection Preventive Maintenance (IPM) Alat Cath Lab - Yeni Pertiwi; M. Febry Rhomadhon; Nur Hadziqoh; Nani Lasiyah; Rino Ferdian (Abdimas Universal, 2022)
Health equipment is a very crucial component in health services. In Indonesian Hospitals, the quality of medical devices is carried out by the Hospital Facility Maintenance Installation, which is abbreviated as IPSRS. Generally, IPSRS staff consists of human resources who have qualifications in Electromedical, Public Health, and Management qualifications. HR who carry out maintenance and repairs, hereinafter referred to as Preventive Maintenance Inspection (IPM) of medical devices, are HR with electromedical qualifications. Cath Lab is the latest technology in the medical world. Therefore, many electromedical technicians do not understand the latest developments in the Cath Lab IPM process. In order to prepare hospital services with quality Cath Lab tools, reliable human resources are needed in carrying out their HDI. For this reason, training on HDI from this Cath Lab equipment is needed. This HDI training was attended by 534 participants from all over Indonesia which was carried out through the Zoom Meetings Application. This training succeeded in increasing the ability of participants by 22.28% from the initial ability of 46.48% to 68.76%. The participants' satisfaction with the reliability of the resource persons, activity themes, communication, committee and media used in the training activities was 86.57% in the very satisfied category.